Assume N is a dividend which is a positive integer with 2 different results.
1 . N is divided by 3 2 with remainder 3 1 .
2 . N is divided by 4 2 with remainder 3 7 .
The congruence can express as N ≡ a m o d b , which a and b are positive integers, with a being the the minimum dividend and g cd ( a , b ) = 1 . Find the value of b − a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very nice. Could you explain a little more how you got to the forms for x , y in terms of t ? (It seems that's the key step.) Does it rely on "knowing" (or calculating) that 1 6 × 1 2 − 2 1 × 9 = 3 , or is there a more systematic way?
@Vincent Huang 's solution is great - I'm just adding this to show a method that can easily be extended to more complicated questions.
Since one of the quotients is a power of two, we can solve this just using parity. Any time we find a number k that must be even, we'll replace it by 2 k ′ ; any that must be odd we'll replace with 2 k ′ + 1 . I am not good at mental arithmetic, so I'll do everything possible to keep numbers small; starting by rewriting the first congruence as N = 3 2 x − 1 and the second as N = 4 2 y − 5 for some x , y : 3 2 x − 1 3 2 x + 4 1 6 x + 2 1 6 x + 2 8 x + 1 8 x + 1 4 x 4 x 2 x 2 x x = 4 2 y − 5 = 4 2 y = 2 1 y , so y is even = 4 2 y ′ = 2 1 y ′ , so y ′ is odd = 4 2 y ′ ′ + 2 1 = 2 1 y ′ ′ + 1 0 , so y ′ ′ is even = 4 2 y ′ ′ ′ + 1 0 = 2 1 y ′ ′ ′ + 5 , so y ′ ′ ′ is odd = 4 2 y ′ ′ ′ ′ + 2 6 = 2 1 y ′ ′ ′ ′ + 1 3
or, letting u = y ′ ′ ′ ′ , we have x = 2 1 u + 1 3 .
Hence N = 3 2 ( 2 1 u + 1 3 ) − 1 = 6 7 2 u + 4 1 5 , ie N ≡ 4 1 5 ( m o d 6 7 2 ) and b − a = 2 5 7 .
Problem Loading...
Note Loading...
Set Loading...
By using Diophantine Equation , let x and y are different quotients:
3 1 + 3 2 x = 3 7 + 4 2 y → 1 6 x − 2 1 y = 3 → { x = 1 2 + 2 1 t y = 9 + 1 6 t
Then insert into original equation:
3 1 + 3 2 ( 1 2 + 2 1 t ) → N = 4 1 5 + 6 7 2 t → N ≡ 4 1 5 m o d 6 7 2 → ( a , b ) = ( 4 1 5 , 6 7 2 )
Therefore, b − a = 2 5 7 .